Nuevas herramientas para el estudio histológico del sistema nervioso - Saavedra C., Humberto (M.C.) (Avances en Ciencias Veterinarias, 1992)
A brief review is given of the use of enzymes and lectines; these vegetal substances are transported through the axonal low in the retrograde as well as in the anterograde direction and are therefore tools to label monosynaptically connected pathways. The weat germ agglutinine conjugated with horseradish peroxidase result in fifty fold increase of the labeling. The utilization of certain neurotropic virus as transneuronal markers are described. Key words: Anterograde, retrograde labeling, transneuronal markers, WGA-HRP, neurotropic virus. Palabras claves: Marcación retrógrada y anterógrada, marcadores transneuronales, WGA-HRP, virus neurotrópicos.